Polymer-ceramic bone bricks for tissue engineering (Transactions on Additive Manufacturing Meets Medicine, 2019)
This paper investigates the use of polymer-ceramic composite scaffolds for bone regeneration. Different ratios between Poly-e-caprolactone (PCL)  and Hydroxyapatite (HA) were considered. Scaffolds were produced using two different lay-down patterns (0/90° and 0/45°) and pore sizes (350?m, 500?m and 700?m). Compressive tests and cell proliferation tests are reported. Human adipose derived stem cells (hADSCs) were used for the biological characterization.